A practical commentary or an exposition with notes on the epistle of James - Manton, Thomas, 1620-1677 (Evansville, IN Jay Green, The Sovereign Grace Book Club)
Includes bibliographical references and index.
First published 1651.
Keywords: Bible. N.T. James -- commentaries